Screening Keseimbangan pada Lansia Menggunakan One Leg Standing Test - Astrid Komala Dewi; Catherine Hermawan Salim; Ribka Sabarina Panjaitan (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
Balance is a crucial component in maintaining independence in the elderly and preventing the risk of falls. Decreased balance function with aging can increase the incidence of falls, impacting the elderly's quality of life. This activity aims to screen balance in the elderly using the One Leg Standing Test (OLST) as a simple measurement tool to assess static balance. The activity was conducted in the elderly community in RT 05/RW 08, Karang Anyar Village, Central Jakarta. The test was conducted by asking participants to stand on one leg, and a time was determined until they lost their balance. The screening results showed variations in balance ability, with some elderly still in the good category, while others showed a decline in balance ability and were at risk of falls. These findings demonstrate the importance of balance training programs, muscle strengthening, and fall prevention education for the elderly. This screening activity is expected to form the basis for planning further health interventions to improve the safety and quality of life of the elderly in the community.